UNDERSTANDING CLASSIC, STRAUSSIAN, AND CONSTRUCTIVIST GROUNDED THEORY APPROACHES - Windy Rakhmawati (Belitung Nursing Journal, 2019)
Grounded theory has been utilized in nursing research in order to develop theory from data. Since there are three approaches in the grounded theory methodology that consist of Classic grounded theory, Straussian grounded theory, and Constructivist grounded theory, thus understanding about perspective of each approach is needed. Those approaches have different points of views regarding the philosophical position, role of literature review, and coding process in data analysis. This review provides an understanding about the grounded theory approaches for researchers particularly the novice researchers, and selects an appropriate approach in their study.